2018
DOI: 10.1111/gwat.12666
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of a Rural Subdivision on Groundwater Quality: Results of Long‐Term Monitoring

Abstract: A rural subdivision in south central Wisconsin was instrumented with monitoring wells and lysimeters before, during, and after its construction to examine the impacts of the unsewered subdivision on groundwater quality and quantity. Prior to construction, the 78-acre (32 ha) site was farmland. Sixteen homes were constructed beginning in 2003. Initial monitoring from 2002 to 2005 showed that groundwater beneath the site had been impacted by previous agricultural use, with nitrate-N values as high as 30 mg/L and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…However, the associations were negative (i.e., implausible and therefore not eligible for model inclusion), likely because more land with housing and septic systems meant there was less land nearby with agricultural activities. Rayne et al (2019) made a similar observation, showing that when an agricultural field near Madison, Wisconsin, was developed into a housing subdivision with septic systems, the number of monitoring wells with NO − 3 -N >10 mg=L declined. The area of fields with NMPs within 229 m was positively associated with having a well with NO − 3 -N >10 mg=L during groundwater recharge.…”
Section: Risk Factors For Well Contamination With Nitrate or Coliformsmentioning
confidence: 71%
“…However, the associations were negative (i.e., implausible and therefore not eligible for model inclusion), likely because more land with housing and septic systems meant there was less land nearby with agricultural activities. Rayne et al (2019) made a similar observation, showing that when an agricultural field near Madison, Wisconsin, was developed into a housing subdivision with septic systems, the number of monitoring wells with NO − 3 -N >10 mg=L declined. The area of fields with NMPs within 229 m was positively associated with having a well with NO − 3 -N >10 mg=L during groundwater recharge.…”
Section: Risk Factors For Well Contamination With Nitrate or Coliformsmentioning
confidence: 71%
“…We have had more than 40 years of salt application since then; one recent study in New York State estimated that 24% of private wells were contaminated with deicing salt and 70% of survey participants stopped using their well water because of safety concerns (Pieper et al 2018). Similar cases of well contamination were reported in Wisconsin, with well-water concentrations exceeding 400 mg Cl − /L (Rayne et al 2019). High concentrations of deicing salt typically occur in wells located near roads in lower elevations or downhill from road networks (Kelly et al 2018).…”
Section: How Are Road Salts Affecting Drinking Water Supplies?mentioning
confidence: 91%
“…Similar cases of well contamination were reported in Wisconsin, with well‐water concentrations exceeding 400 mg Cl − /L (Rayne et al . 2019). High concentrations of deicing salt typically occur in wells located near roads in lower elevations or downhill from road networks (Kelly et al .…”
Section: How Are Road Salts Affecting Drinking Water Supplies?mentioning
confidence: 99%
“…An evolved version of Perera and coauthor's methodology was used to estimate chloride in groundwater concentrations in Guelph, Ontario, Canada, a city reliant on groundwater, and proved effective ( R 2 of 0.84 between calculated groundwater recharge chloride concentration and measured groundwater chloride concentrations) (Betts et al, 2015; Salek et al, 2018). Additionally, many studies have found that land use changes , such as increasing suburbanization and percentage of paved surfaces in an area, accelerate the increase of chloride concentrations (Daley et al, 2009; David et al, 2016; Rayne et al, 2019). Another Canadian study in Toronto evaluated how future chloride contamination of groundwater supply resources could limit urban growth as “significant deterioration” of groundwater quality occurs at chloride concentrations above 250 mg/L (Howard & Maier, 2007).…”
Section: Introductionmentioning
confidence: 99%